An institutional and governance approach to understand large-scale social housing construction in China. (August 2018) - Lin, Yanliu
Abstract: The construction of social housing in Chinese cities on a massive scale is considered necessary to meet the urgent housing needs of low- and middle-income households. This article develops an institutional and governance approach to understand large-scale social housing construction in China. It takes Guangzhou as a case study to illustrate the problems faced by many large-scale social housing neighborhoods that have recently been built in the suburbs of Chinese cities, and the impact of institutions and governance activities on the creation of such neighborhoods. It studies the evolution of social housing systems within different welfare regimes in Guangzhou, and examines the influence of institutional factors and the roles of and relationships between various stakeholders on the social housing projects. Suggestions regarding institutional reforms, innovative governance, and new spatial arrangements are given for the sustainable social housing construction in China.